Power misses II : cinema, Asian and modern - James, David E., 1945- (New Barnet, Herts : John Libbey Publishing Ltd, 2020)
Like David James' earlier collection of essays, Power Misses: Essays Across (Un)Popular Culture (1996), the present volume, Power Misses II: Cinema, Asian and Modern is concerned with popular cultural activity that propose alternatives and opposition to capitalist media. Now with a wider frame of reference, it moves globally from west to east, beginning with films made during the Korean Democracy Movement, and then turning to socialist realism in China and Taiwan, and to Asian American film and poetry in Los Angeles. Several other avant-garde film movements in L.A. created communities resistant to the culture industries centered there, as did elements in the classic New York avant-garde, here instanced in the work of Ken Jacobs and Andy Warhol. The final chapter concerns little-known films about communal agriculture in the Nottinghamshire village of Laxton, the only one where the medieval open-field system never suffered enclosure. This survival of the commons anticipated resistance to the extreme and catastrophic forms of privatization, monetization, and theft of the public commonweal in the advanced form of capitalism we know as neoliberalism.
Foreword -- Im Kwon-taek: Korean national cinema and Buddhism -- Im Kwon-taek's use of nativist Korean culture as allegories of cinema: Ch'unhyang, Chihwaseon, and Hanji -- The name of a desire: recollections of socialist realism in East Asian art cinema -- Tradition and the movies: the working-class Asian American avant-garde in Los Angeles -- The sons and daughters of Los: culture and community in Los Angeles -- Toward a geo-cinematic hermeneutics/The city as means of production: representations of Los Angeles in Killer of sheep and Water and power -- Expanded cinema in Los Angeles: the single wing turquoise bird -- L.A.'s hipster cinema -- Film as an instrument of thought, cinema as an augury of redemption: Ken Jacobs' The sky socialist -- "Apotheosis into tragedy": catoptrics of self in Andy Warhol's Lupe -- Letter to Paul Arthur (Letter with endnotes) -- Agricultural revelation: land, labor, and voice in three films about Laxton.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Motion pictures -- East Asia -- History; Motion picture industry -- East Asia; Motion pictures -- California -- Los Angeles -- History; Asian Americans in motion pictures; Cinéma -- Californie -- Los Angeles -- Histoire; Américains d'origine asiatique au cinéma.; Asian Americans in motion pictures; Motion picture industry; Motion pictures; California -- Los Angeles; East Asia; History & Criticism; Asia; HISTORY; Film & Video; PERFORMING ARTS; Electronic books; History